2008
DOI: 10.1007/s10440-007-9187-x
|View full text |Cite
|
Sign up to set email alerts
|

Variational Approach to the Inviscid Compressible Fluid

Abstract: It is well-known that not every partial differential equation admits a variational formula. A rigorous proof of the existence of a variational principle is very difficult. In this paper, the semi-inverse method proposed by Ji-Huan He is used to construct a variational principle for a one-dimensional inviscid compressible fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…(58) are not equal indicates that a variational principle cannot be derived for the differential Eqs. (49) and (53) in their present form. This difficulty can be overcome by transforming the dependent variables u 1 , u 2 , w 1 and w 2 as follows 17…”
Section: Variational Formulationmentioning
confidence: 68%
See 3 more Smart Citations
“…(58) are not equal indicates that a variational principle cannot be derived for the differential Eqs. (49) and (53) in their present form. This difficulty can be overcome by transforming the dependent variables u 1 , u 2 , w 1 and w 2 as follows 17…”
Section: Variational Formulationmentioning
confidence: 68%
“…(49) and (53) correspond to the Euler-Lagrange equations of the variational functional (54) given by…”
Section: Variational Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tao [14,15] found that He's variational method was very simple and effective. Other applications of He's variational method are available in Refs.…”
Section: He's Variational Methodsmentioning
confidence: 99%